2018
DOI: 10.1039/c8cp02250j
|View full text |Cite
|
Sign up to set email alerts
|

SO2absorption in EmimCl–TEG deep eutectic solvents

Abstract: Deep eutectic solvents (DESs) based on 1-ethyl-3-methylimidazolium chloride (EmimCl) and triethylene glycol (TEG) with different molar ratios (from 6 : 1 to 1 : 1) were prepared. FTIR and theoretical calculation indicated that the C2-H on the imidazolium ring form hydrogen bonds with the hydroxyl group rather than the ether O atom of the TEG. The EmimCl-TEG DESs can efficiently capture SO2; in particular, EmimCl-TEG (6 : 1) can capture 0.54 g SO2 per gram of solvent at 0.10 atm and 20 °C, the highest absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…The results showed that the prepared DESs demonstrate excellent performance in separating NH 3 , not only with high efficiency and selectivity but also with reversible absorption of NH 3 . Recently, an interesting study reported by Yang et al , investigated the absorption of SO 2 by DESs formed by 1-ethyl-3-methylimidazole chloride ([EMIM]­[Cl]), ethylene glycol (EG), and triethylene glycol (TEG) under different conditions. The results show that all the [EMIM]­[Cl]–EG and [EMIM]­[Cl]–TEG solvents have a high capture efficiency for SO 2 , and the solubility of SO 2 increases with increasing [EMIM]­[Cl] concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the prepared DESs demonstrate excellent performance in separating NH 3 , not only with high efficiency and selectivity but also with reversible absorption of NH 3 . Recently, an interesting study reported by Yang et al , investigated the absorption of SO 2 by DESs formed by 1-ethyl-3-methylimidazole chloride ([EMIM]­[Cl]), ethylene glycol (EG), and triethylene glycol (TEG) under different conditions. The results show that all the [EMIM]­[Cl]–EG and [EMIM]­[Cl]–TEG solvents have a high capture efficiency for SO 2 , and the solubility of SO 2 increases with increasing [EMIM]­[Cl] concentration.…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 , WO 3 and TiO 2 ), have been proposed considering their selectivity, response time and recovery time [15,16,17] Nevertheless, due to the high temperature requirements of the processes that involve proposed semiconductors for SO 2 raised concerns on their high power consumption requirement for such processes [18,19]. Thus, tackling the SO 2 capture problem at low-to-moderate temperature conditions is still one of the major concerns and if achieved it will be a major milestone for deploying effective replacements to currently used materials for capturing SO 2 [20,21,22]. For this purpose, during the past decade, ionic liquids (IL) have been considered effective greenhouse gas capture solvents due to their properties such as good thermal and chemical stability, non-flammability and almost null vapor pressure [23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of DES via low-cost sources including natural HBA and HBD, predictable and almost null toxicity and total biodegradability have made both industry and academia consider DES as alternative solvents for gas capture and separation processes in within the green chemistry framework. Having said that, in recent years there has been increasing interest in the utilization of DES for gas capture especially on CO 2 capture and separation [37,38,39,40,41] however there are only a handful of studies that deal with the nature of the interaction between DES and SO 2 [14,20,21,22,42,43,44,45,46,47,48,49,50]. Most of the available few studies are in experimental basis and simply deal with determination of SO 2 solubility at low pressures in select DES systems [51].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that imidazolium-based ILs exhibited considerable SO 2 absorption capacity. Therefore, Yang et al [41][42][43] designed a series of EmimCl-based DESs, including EmimCl:EG DES (1:1), EmimCl:triethylene glycol(TEG) DES (1:1), and EmimCl:succinonitrile (SN) DES (1:1), for efficient SO 2 capture and obtained the corresponding absorption capacity of 1.03, 0.91, and 1.13 g SO 2 /g DES, respectively, at 293.15 K and 101 kPa. It showed that the efficiency of imidazolium cation is better than that of ammonium.…”
Section: Imidazolium-based Dessmentioning
confidence: 99%